A RARE CASE OF SUBCONJUNCTIVAL HEMORRHAGE POST COVID-19 mRNA VACCINE: A CASE REPORT: A Rare Case of Subconjunctival Hemorrhage Post COVID-19 mRNA Vaccine: A Case Report - Jovita Jutamulia; Arlin Chyntia Dewi; Salma Salsabila; Vicky Octaviani (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction: Concurrently with the administration of COVID-19 vaccine, adverse event following immunization (AEFI) began to be reported. Some reactions involve various systems of the human body, including the ocular system. Although uncommon, subconjunctival hemorrhage also can be found, as shown in this report. Case Report: We present a case of a 68-year-old woman with subconjunctival hemorrhage a couple hours before admission. Patient also came with complaints of sudden redness and pain in left eye. Two days prior, she had her first dose of Moderna vaccine. Left eye examination revealed hemorrhage on conjunctiva with normal visual acuity. Other ocular examinations couldn’t be done due to the lack of facilities and severe pain. No other symptoms were mentioned. Patient was advised to be referred to an ophthalmologist, but she refused. After a month, the patient reportedly experienced similar complaints after receiving the second dose of Moderna vaccine. another redness and discomfort in her left eye. Her left eye was red, itched, and swollen. However, she still refused to go to an ophthalmologist. Oral analgesic, oral antihistamine, and artificial tears were given. The symptoms were completely resolved in a couple days. Conclusion: Subconjunctival hemorrhage may occur as mRNA Vaccine AEFI specifically in patients with underlying disease, however further research is needed.